Epistemologi Burhani dalam Pembelajaran Fiqih di Madrasah Ibtidaiyah - Fauziah, Kurniatun Nailatin; Saleh, Yusuf Yusian Septianto (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Burhani epistemology is a method and framework of logical thinking that focuses on considering various points of view and examining arguments carefully before arriving at a final conclusion. Learning fiqh at madrasah ibtidaiyah is a form of education related to the basic laws of fiqh, so it requires reasoning and a solid foundation in order to know with certainty the purpose of the fiqh laws. The aim of the research is to analyze and explain burhani epistemology, explain and describe fiqh learning in ibtidaiyah madrasas, and analyze the implementation of burhani epistemology in fiqh learning in ibtidaiyah madrasas. The research method used is a literature study which takes data sources from research journals and books. The results of this research found that burhani epistemology is a method for forming logical thinking for students, especially in learning fiqh at madrasah ibtidaiyah because it is able to shape students' reasoning regarding the fiqh laws being studied.